ICP4, the major regulatory protein of herpes simplex virus, shares features common to GTP-binding proteins and is adenylated and guanylated. - Blaho, J A (1991)
Infected cell protein 4 (ICP4), the product of the alpha 4 gene, regulates herpes simplex virus 1 and herpes simplex virus 2 gene expression at the transcriptional level both positively and negatively. Previous studies have shown that ICP4 is extensively modified posttranslationally. We report that ICP4 was labeled in isolated nuclei of infected cells by [alpha-32P]GTP or [alpha-32P]ATP. The labeling of ICP4 by [alpha-32P]GTP or [alpha-32P]ATP required excess GTP, ATP, GDP, and ADP and occurred also in the presence of excess GTP(gamma)S. While GDP and ADP activated the labeling process, only GTP and ATP labeled ICP4. Accumulation of labeled ICP4 was favored at temperatures from 15 to 27 degrees C and in the presence of okadaic acid. The conditions for labeling ICP4 with [alpha-32P]GTP or [alpha-32P]ATP and the stability of the labeled protein were different from those of ICP4 labeled with [gamma-32P]ATP. Labeling studies with tritiated ATP and GTP showed that ICP4 is nucleotidylated, and chemical degradation of ICP4 labeled with [alpha-32P]GTP yielded ribose-5-phosphate. Pulse-chase experiments indicated that the adenylation and guanylation are independent processes. These results, and the observation that ICP4 contains four regions which possess consensus GTP-binding elements, suggest that ICP4 may belong to a class of GTP-binding proteins which function in transcriptional transactivation.